2018
DOI: 10.1111/jfbc.12545
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new beverage made of dates vinegar and garlic juice in improving serum lipid profile parameters and inflammatory biomarkers of mildly hyperlipidemic adults: A double-blinded, randomized, placebo-controlled study

Abstract: A beverage made from date vinegar and garlic juice was recently developed for use by people who wish to attain maximum quantities of both vinegar and polyphenols for their health and do not like to use vinegar and garlic directly in their daily diet. Fifty hyperlipidemic adults consumed two cups (500 mL) of either the new beverage or a placebo daily over a period of 7 weeks. Plasma lipids, inflammatory biomarkers, urea, creatinine, potassium, and β‐carotenoid concentrations were measured before and after each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…A similar effect was reported during 13 weeks of dates supplementation in hamsters [14]. Another possible explanation could be that the increased concentrations of plasma carotenoids released during the digestion of dates competed with dietary lipids for assimilation and transport in lipoproteins, subsequently leading to lower cholesterol levels [27]. Contrary to our results, the study of Rock et al [28] found no statistically significant effect of date consumption in healthy human subjects on total cholesterol and HDL level.…”
Section: Discussionsupporting
confidence: 62%
“…A similar effect was reported during 13 weeks of dates supplementation in hamsters [14]. Another possible explanation could be that the increased concentrations of plasma carotenoids released during the digestion of dates competed with dietary lipids for assimilation and transport in lipoproteins, subsequently leading to lower cholesterol levels [27]. Contrary to our results, the study of Rock et al [28] found no statistically significant effect of date consumption in healthy human subjects on total cholesterol and HDL level.…”
Section: Discussionsupporting
confidence: 62%
“…Vinegar has been found to possess inhibitory effects against immunoglobulin E (IgE) production, immune cell infiltration, Th1 or Th17 responses, and Toll-like receptor (TLR)4-induced inflammatory response [10][11][12]. Moreover, vinegar supplementation reduced the levels of interleukin-6 (IL-6), an inflammatory cytokine, and the biomarkers nitric oxide (NO) and TNF-α in a clinical study [13][14][15][16]. Recently, vinegars have been reported to reduce body fat and glucose levels, as well as exert anti-oxidant, anti-tumor, and anti-microbial effects [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Dates contain fiber vital mineral (iron, selenium fluorine, and calcium) and vitamins (Vayalil, ). Results have shown that extracts from dates have exposed free radical scavenging activity, immunomodulatory, and antimutagenic activities, (Allaith, ; Khan, Sarwar, Wahab, & Haleem, ) and dates have cardioprotective, anti‐inflammatory, antiobesity, and antihypertensive effects (Ali, Ma, Ayim, & Wali, ; Ali, Ma, Rashid, et al, ). In the past, dates' vinegar did not receive the attention it deserves due to limited literature about the fruit.…”
Section: Introductionmentioning
confidence: 99%